Forecasting the Incidence of Testis Cancer in Europe from 2012-2035 - Ali Asghar VALIPOUR; Mahdi MOHAMMADIAN; Abdollah MOHAMMADIAN-HAFSHEJANI; Sarah ISLAMIE FARSANI (Tehran University of Medical Sciences, 2017)
Forecasting the Incidence of Testis Cancer in Europe from 2012-2035